Volatile aldehydes in the mainstream smoke of the narghile waterpipe - Al Rashidi, M.; Shihadeh, A.; Saliba, N.A. (Food and chemical toxicology, 2008)
Very little is known about the quality and quantity of toxicants yielded by the narghile, a subject of increasing importance as this method of tobacco smoking has become popular all over the world. This study is concerned with the identification and quantification of volatile aldehydes in the gas and particle phases of mainstream narghile smoke generated using a popular type of flavored ma’ssel tobacco mixture. These compounds were analyzed based on a modified version of the Environmental Protection Agency compendium method TO-11A. Using a standardized smoking machine protocol consisting of 171 puffs, 2.6 s puff duration and 17 s inter puff interval, the average yields of formaldehyde, acetaldehyde, acrolein, propionaldehyde and methacrolein were 630, 2520, 892, 403, and 106 μg/smoking session, respectively. The results showed that none of the aldehydes identified in this study are found in the particulate phase of the smoke, except for formaldehyde for which the partitioning coefficient was estimated as K p = 3.3 × 10 −8 μg/m 3. Given previously reported lung absorption fractions of circa 90% for volatile aldehydes, the yields measured in this study are sufficient to induce various diseases depending on the extent of exposure, and on the breathing patterns of the smokers.